Effect of silicon on the oxidation resistance of 9 wt.% Cr heat resistance steels in 550 °C lead-bismuth eutectic. (October 2016) - Wang, Jian; Lu, Shanping; Rong, Lijian; Li, Dianzhong; Li, Yiyi
Highlights: The oxide film presents a three-layers structure. The oxidation is the diffusion controlled process and fits for the parabolic law. Si improves the oxidation resistance for 9 wt.% Cr steel in lead-bismuth eutectic. The continuous dense Cr2 O3 and SiO2 mixture layer improves the oxidation resistance. Abstract: The oxidation resistance of 9 wt.% Cr heat resistance steel with silicon content ranging from 0 to 1.36 wt.% in 550 °C lead-bismuth eutectic was investigated. The silicon content had little influence on the macro-structure of the oxide film. The oxide film presented a three-layers structure. The outer layer was PbO·xFe2 O3 and Fe3 O4 while the inner layer was mainly FeCr2 O4 . The formation of thin continuous dense Cr2 O3 and SiO2 mixture layer impeded the growth of Fe-rich oxide film, which improved the oxidation resistance in high silicon content. A oxidation process model was put forward to well explain this phenomenon.